Pengembangan Modul Pembelajaran IPA SD Berbasis Brain Based Learning (BBL) - Maesarani; Sucilestari, Ramdhani; Hamzan (CAHAYA: Journal of Research on Science Education, 2023)
This study developed a Brain Based Learning-based sciencelearning module on the sub-matter of the function of human and animal organs. In the module there are very detailed learning objectives so that student learning activities become directed in achieving learning objectives that are valid and practical to use in learning. This research is a development research, namely, developing learning modules using the ADDIE development method. The selection of the ADDIE method is based on the consideration that the ADDIE method is oriented towards learning products. The ADDIE research and development method consists of five stages, namely, the Analysis (Analysis), Design (Desigen), Development (Deplovment), Implementation (Implementation), and Evaluation (Evaluation) stages.  In the research, the trial was conducted at SDN 1 Pusuk Lestari. The research subjects used were class V students as many as 18 students. The assessment instrument used is a validation sheet and student response questionnaire. Based on the results of the feasibility trial, the learning module developed was included in the feasible/valid category. To determine the feasibility of the developed learning module, researchers used material expert validators and media experts using a questionnaire assessment in the form of a Likert scale. The average percentage score obtained from material experts in the first validation was 27.38% while the second validation score obtained was 75% and the media expert validator in the first validation was 31.25% while the second validator produced 75% of the results of the assessment of the two experts, the learning module was categorised as feasible/valid to use. At the small group trial stage, the percentage score obtained was 82.16%, while the large group trial obtained a percentage of 87.22%, which was classified as good.